Role of CD56-expressing immature biliary epithelial cells in biliary atresia - Zhang, Rui-Zhong (World journal of gastroenterology : WJG, 2016)
AIM: To analyze the clinical and pathological parameters and expression of the neural cell adhesion molecule(CD56) in patients with biliary atresia(BA).METHODS: Established clinical laboratory markers of hepatic function, including enzyme activity, protein synthesis, and bilirubin metabolism, were evaluated in patients with BA and compared with those in patients with choledochal cysts and neonatal hepatitis. Pathological changes in tissue morphology and fibrosis were examined by histological and tissue collagen staining. Immunohistochemical staining for the biliary epithelial cell markers CD56 and CK19 together with the Notch signaling related molecules Notch1 and Notch2 was performed in the context of alterations in the structure of intrahepatic biliary ducts.RESULTS: Differences in some clinical laboratoryparameters among the three diseases examined were observed, but they did not correlate with the pathological classification of fibrosis in BA. Immunohistochemical staining showed the presence of CD56-positive immature bile ducts in most patients(74.5%) with BA but not in patients with choledochal cysts or neonatal hepatitis. The number of CD56-expressing cells correlated with disease severity, with more positive cells present in the later stages of liver damage(81.8% vs 18.2%). Furthermore, bile plugs were mainly found in CD56-positive immature biliary ducts. Notch signaling was a key regulatory pathway in biliary duct formation and played a role in tissue fibrosis. Notch1 was co-expressed in CD56-positive cells, whereas Notch2 was found exclusively in blood vessels in the portal area of patients with BA. CONCLUSION: The maturation of biliary epithelial cells and the expression of Notch may play a role in the pathogenesis of BA.